Real-Time BPMN Website Menggunakan Teknologi MERN Stack - Ricky Handoyo; Leo Willyanto Santoso; Alexander Setiawan (Jurnal Infra, 2019)
At present, technology is a tool developed to help facilitate human activities. The making of complex and many bpmn diagrams is impossible to do by one or two people and also there are people who do an examination of the diagram that has been made. The current system is done by utilizing file sharing where BPMN files that have been done are sent via email. Therefore we need a system where a project can be accessed by several users directly.The making of real-time bpmn website is designed by utilizing the MERN stack technology as a single page application and javascript library which is used in making websites, especially library bpmn js for making diagrams and sockets IO for real-time two-way communication between users and system.The final result of this paper is a real-time website bpmn is used to help users make bpmn diagrams that can be done by several users. The presence of features such as sharing systems, real-time diagrams, and real-time chat are made for users to be able to share projects and make diagrams together.